Answer:
Explanation:
We can factor the numerator and denominator as;
(
x
−
2
)
(
x
−
1
)
2
x
(
x
−
1
)
We can now cancel common term in the numerator and denominator:
(
x
−
2
)
(
x
−
1
)
2
x
(
x
−
1
)
⇒
x
−
2
2
x
However, we cannot divide by
0
so we must exclude:
2
x
=
0
⇒
x
=
0
and
x
−
1
=
0
⇒
x
1
x
2
−
3
x
+
2
2
x
2
−
2
x
=
x
−
2
2
x
Where:
x
≠
0
and
x
≠
1
Or
x
2
−
3
x
+
2
2
x
2
−
2
x
=
x
2
x
−
2
2
x
=
1
2
−
1
x
Where:
x
≠
0
and
x
≠
1
Step-by-step explanation:
G - 24 = 75
g = 75 + 24
g = 99
Final answer g = 99
Answer:
My favorite color is aqua and pink
Step-by-step explanation:
So we are trying to get the “y” alone, so to undo the division by -8, we will multiply both sides by -8, then simplify.
(-8) y/(-8) = (-8) 1/16
y = -8/16
and simplified:
y = -1/2
Solve for p by simplifying both sides of the equation, then isolation the variable
p = 1 + m/2
Hope this helps! :)